Determinan Profil Risiko Terhadap Performance Bank Pembiayaan Rakyat Syariah Di Provinsi Sumatera Barat - Nur Azlina; Husni Shabri; Ibnu Qizam (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
This study aims to analyze the effect of risk profile on the performance of Islamic Rural Bank (BPRS) in West Sumatra Province. This type of research is a field research with a quantitative approach. The samples in the study were seven BPRS in West Sumatra Province that have been operating sharia since 2019. Secondary data in the form of annual financial statements of each BPRS for the period 2019-2022. The analysis technique used panel data regression. The results showed that the credit risk profile using the Non Performing Financing ratio and liquidity risk using the Financing to Deposit Ratio partially had no significant effect on the performance of BPRS as measured using the Return on Asset ratio. However, both risk profiles simultaneously have a significant effect on the performance of BPRS with a coefficient of determination of 96%. The practical implication of this research is that credit risk and liquidity risk must be managed simultaneously, including other risks faced by banks because they have a very strong influence on bank performance.